PENGARUH KELOMPOK REFERENSI INFORMAL UTAMA TERHADAP KEPUTUSAN CALON MAHASISWA MEMILIH PRODI MANAJEMEN UNIVERSITAS MUHAMMADIYAH GRESIK - ERNI KURNIATI (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The purpose of this study was to determine whether or not the influence of the main informal reference group of family and friends in the decision selecting candidates who study programs Muhamadiyah Gresik University management either partially or simultaneously. The hypothesis formulated in this research is influential family and friends either partially or simultaneously to the applicant's decision. Analysis tools used logistic regression, hypothesis testing using chi-square test and wald test. The calculations show that the free variables of family0 (x1) and friends (x2), which is partially or simultaneously have an influence on a candidate's decision. value for the family of (2.954), friends (1.663) which means that the influence of larger family than friends. Based on the results of this analysis is the University of Muhammadiyah Gresik management courses in particular should make promotions more to prospective students interested in college at the University of Muhammadiyah Gresik.